Slavist as a Scout: French School of Oriental Languages and Russian Revolution in 1918 - Yu. M. Galkina (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
Based on the materials of the National Archives of France, the activity of graduates-Slavists of the School of Oriental Languages (Paris) in 1918 in Russia is considered. The article focuses on philologists and dip-lomats: A. Mazon, H. Gauquié, J. Sichel-Dulong, P. Blay. Their activity in Soviet Russia and their view of the events taking place in the country are reconstructed on the basis of letters sent to the director of the School of Oriental Languages — P. Boyer. It is shown that many of the ideas declared by specialists in Russian studies are a reflection of the mentality prevailing in the French political elite: the idea of the imminent fall of the Bolshevik power, confidence in the German trace of the Russian revolution, the desire to view the political transformations of Soviet Russia through the prism of French historical and parliamentary experience. It is noted that H. Gauquié, took the most critical position in understanding the events in Russia, placing the needs of the Russian person at the center of his analytical work. The novelty of the research lies in the consideration of the role of France in the escalation of the Civil War in Russia, which for a long time was in the “blind spot” of research interest. The author of the article reconstructs the contacts of the School’s alumni with the anti-Bolshevik underground. The role and importance of scientists in supporting the intelligence activities of France in Soviet Russia are revealed.